2006
DOI: 10.1590/s1678-77572006000600009
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of hard chairside reline resins to a rapid polymerizing denture base resin before and after thermal cycling

Abstract: Purpose:This study assessed the shear bond strength of 4 hard chairside reline resins (Kooliner, Tokuso Rebase Fast, Duraliner II, Ufi Gel Hard) to a rapid polymerizing denture base resin (QC-20) processed using 2 polymerization cycles (A or B), before and after thermal cycling.Materials and Methods:Cylinders (3.5 mm x 5.0 mm) of the reline resins were bonded to cylinders of QC-20 polymerized using cycle A (boiling water–20 minutes) or B (boiling water; remove heat-20 minutes; boiling water–20 minutes). For ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…27,28 Moreover, the components used for chemical activation in addition to thermal activation, contained in the short-cycle resins, may be responsible for the results shown by the QC resin. 29 These results are in agreement with those by Hersek et al, 20 who evaluated the color stability of acrylic resins in three colorants used in food and verified that LU followed by QC presented the greatest color changes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…27,28 Moreover, the components used for chemical activation in addition to thermal activation, contained in the short-cycle resins, may be responsible for the results shown by the QC resin. 29 These results are in agreement with those by Hersek et al, 20 who evaluated the color stability of acrylic resins in three colorants used in food and verified that LU followed by QC presented the greatest color changes.…”
Section: Discussionsupporting
confidence: 91%
“…1,[20][21][22]29 The dark pigment of W and its low pH can cause drastic staining, negatively affecting the surface integrity by softening the matrix. 20 In this study, only OC did not show a statistically significant color change when immersed in W (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…It was also stated that Eclipse can be relined using the same Eclipse material as well as with other conventional autopolymerized materials. So far, no study has reported on the bond strength of Eclipse as compared to many reports available with PMMA denture base polymer 8,13,14–17 . This study showed that for all reline materials excluding Eclipse reline, the shear bond strengths to PMMA were higher than the strength of corresponding reline materials to UDMA polymer.…”
Section: Discussionmentioning
confidence: 58%
“…As adhesion depends on the penetration of polymerizable monomer of reline material into the denture network, 6 higher molecular weight of IBMA (isobutyl methacrylate) monomer available in Kooliner might have limited the monomer penetration 6,9,14 . In contrast, Neppelenbroek et al 17 found that Kooliner reline showed mixed modes of failure to PMMA base. The denture surface, however, was treated with MMA monomer, which might explain the improved bonding 5 …”
Section: Discussionmentioning
confidence: 99%
“…In vitro simulation of intraoral changes using thermal cycling can greatly affect the mechanical integrity of the liner/denture interface, initiating crack propagation; 28,29 however, the effect of thermocycling is inconclusive and material dependent 9 . It may increase or decrease bond strength 19,28,30–34 …”
mentioning
confidence: 99%